Description sentence between nominative and verbal and different grammarians in it - Harba, Mohamed Bashir; Arifin, Zamri; Zainal, Hakim (Arab Journal for Sciences and Research Publishing, 2021)
Arabic language is one of the richest languages in its grammatical rules. Linguistic research, in its broad sense, has no limit. The grammatical dispute is nothing but a kind of different views, and the task of the grammatical researcher when examining a sentence is to classify it and explain how it is constructed. The research aims to identify the reality of the adjectival sentence, and its position in the Arabic sentence. The research problem here is to identify the adjectival phrase either as nominative or verbal, or is it something else, as it has a double character represented in the difference in its pronunciation from its meaning. In pronunciation, it is a noun, but in the meaning it is a verb-like. The paper also examines the views of both the Basris and the Kufis in the issue, and their arguments. The paper provides what is permissible and what is not in the i’rab, the similarity between adjective and verb, and the difference of grammarians in the adjectival predicate. The paper executes the descriptive analytical method. The research findings are:1- There are three types of sentences in Arabic language: the nominative sentence, verbal sentence, and the adjectival sentence.2- The study manages to reconcile between the different views in the adjectival sentence in terms of both verbal and nominative sentences.3- The study also justifies this division.4- These findings help to make grammar easier for the learners to avoid the interpretation that weighed heavily on grammar.
Keywords: Description; Sentence; Grammar; Study; Disagreement